PENINGKATAN PEMAHAMAN KONSEP FISIKA DAN AKTIVITAS MAHASISWA MELALUI PhET SIMULATION - Elisa Elisa; Ainun Mardiyah; Rizky Ariaji (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2017)
Understanding the concept as one of the keys to success in studying science especially Physics, so do not have to memorize the formula but enough just by understanding the concept alone. Based on observations during community research activities, some positive results were obtained: Participants showed very high attention to the material using PhET Simulation.From the preliminary test in cycle I the pretest score of about 10% is able to answer to 77.5%, while in cycle II the value of the dropper about 20% increased to 97.5%. While for the activity of students which cover the realm of ability to use PhET Simulation from 73,75% in cycle I increase to 85% in cycle II, Inenthusiasm Attitude enthusiasm using PhET Simulation from 75% in cycle I increased to 86,25% in cycle II, In the field of cooperation in the group using PhET Simulation of 72.5% in the first cycle increased to 86.25% in cycle II. In the realm of the ability to use worksheets in PhET Simulation from 75% in cycleI increased to 88.75% in cycle II. In the sphere of participation in the discussion using PhET Simulation from 75% in the first cycle increased to 86.25% in cycle II. The result of the research is the increasing of concept comprehension and the increasing of student learning activity.Keywords:PhET Simulation, Conceptual Understanding, Learning Activities